Follow-up magnetic resonance imaging of Löffler endocarditis: a case report. Issue 6 (9th November 2020) - Ito, Shinya; Isotani, Akihiro; Yamaji, Kyohei; Ando, Kenji
Abstract: Background : Löffler endocarditis is a condition characterized by cardiac infiltration of eosinophils. Cardiac magnetic resonance imaging (MRI) is a modality for the diagnosis of myocardial damage. Case summary : This is the case of a 77-year-old man with acute decompensated heart failure who was admitted. Transthoracic echocardiography showed preserved left ventricular (LV) systolic function along with LV thrombi attached to the septo-apical wall and the posterior wall, consistent with Löffler endocarditis. Cardiac MRI revealed obliteration of the LV apex and partial filling of the LV cavity, as well as near circumferential subendocardial late gadolinium enhancement (LGE) in the mid- and apical segments. T2-weighted images showed a near circumferential high-intensity area of the LV subendocardial muscle in the mid- and apical segments. High-dose corticosteroids and intravenous heparin were initiated, followed by maintenance warfarin therapy. At 18 months, follow-up cardiac MRI revealed the disappearance of the LV thrombi, and a reduction of LGE, as well as high-intensity areas in the T2-weighted images. Discussion : The high-intensity area of T2-weighted images indicate the presence of subendocardial oedema. Eosinophil-mediated heart damage evolves through three stages: (i) acute necrotic, (ii) thrombotic, and (iii) fibrotic stages. Since the deposition of toxic eosinophil granule proteins and eosinophil infiltration injured the endocardium, the first-line treatment for Löffler endocarditis is corticosteroid therapy. In this case, LGE in the subendocardium and the high-intensity area in the T2-weighted images were reduced at 18 months. High-intensity areas of T2-weighted images in the acute phase might indicate the possibility of therapeutic response to corticosteroid therapy.